A Role of Ion Channels in the Endothelium-Independent Relaxation of Rat Mesenteric Artery Induced by Resveratrol - Ljiljana Gojkovic-Bukarica; Aleksandra Novakovic; Vladimir Kanjuh; Marko Bumbasirevic; Aleksandar Lesic; Helmut Heinle (Elsevier, 2008)
Recently it has been suggested that resveratrol relaxes different isolated arteries. The present study addressed the question whether different ion channels are involved in the endothelium-independent mechanism of vasodilatation induced by resveratrol. For that purpose, we tested the action of resveratrol on the rat mesenteric artery without endothelium. Resveratrol induced concentration-dependent relaxation of rat mesenteric artery. Among the K+-channel blockers, 4-amynopiridine (4-AP) moderately antagonized the resveratrol-induced relaxation, while glibenclamide, tetraethylammonium chloride, charybdotoxin, margatoxin, and barium chloride did not inhibit resveratrol-induced vasorelaxation. In rings, precontracted with 100 mM K+, the relaxant responses to resveratrol were highly significantly shifted to the right compared to those obtained in rings precontracted with phenylephrine, but resveratrol-induced maximal relaxation was only slightly affected. In order to minimize the influence of K+ channels and voltage-gated Ca2+ channels (VGCCs) in vascular smooth muscle, the third contraction was made by 100 mM K+ in the presence of nifedipine. The relaxant response to resveratrol was abolished. Thus, the mechanism of vasorelaxation induced by resveratrol probably involves activation of 4-AP-sensitive K+ channels. Its ability to completely relax the mesenteric artery precontracted with K+-rich solution suggests that K+ channel-independent mechanism(s) are involved in its vasorelaxant effect. It seems that interaction with VGCCs plays a part in this K+ channel-independent effect of resveratrol. Keywords:: resveratrol, rat mesenteric artery, ion channel, vasorelaxation, K+ channel